Learning Management System-Mediated e-Tutorials in Mathematics Education: A Case Study of South Africa - Kigundu, Stephen (Yayasan Keluarga Guru Mandiri, 2026)
The study examines the impact of LMS-mediated e-tutorials on student engagement and learning outcomes in mathematics at a South African university. Grounded in constructivist theory, it explores how interactive LMS tools enhance engagement and knowledge construction. The research follows a qualitative case study approach within the interpretivist paradigm, focusing on student performance, learning strategies, perceptions, and system usability. A convenience sample of 129 first-year mechanical engineering students was selected. Data were collected through questionnaires, interviews, observations, screen capture videos, and journals. Thematic analysis identified key patterns related to learning outcomes, student actions, emotional responses, and system affordances. Findings indicate that LMS-mediated e-tutorials enhance student engagement and performance, particularly when they incorporate interactive features and personalized feedback. However, technical challenges, such as rigid input requirements, hinder optimal engagement. Students adopted problem-solving strategies like rough work and social collaboration. The study highlights the potential of LMS tools to bridge learning gaps in mathematics education. Recommendations include enhancing system flexibility, improving feedback mechanisms, fostering collaboration, and incorporating gamification. Continuous evaluation and refinement of LMS features are crucial to maximizing their effectiveness across diverse educational contexts.